Mastering Python for networking and security : leverage Python scripts and libraries to overcome networking and security issues - Manuel Ortega, José (Packt Publishing Ltd., 2018)
Master Python scripting to build a network and perform security operations Key Features Learn to handle cyber attacks with modern Python scripting Discover various Python libraries for building and securing your network Understand Python packages and libraries to secure your network infrastructure Book Description It's becoming more and more apparent that security is a critical aspect of IT infrastructure. A data breach is a major security incident, usually carried out by just hacking a simple network line. Increasing your network's security helps step up your defenses against cyber attacks. Meanwhile, Python is being used for increasingly advanced tasks, with the latest update introducing many new packages. This book focuses on leveraging these updated packages to build a secure network with the help of Python scripting. This book covers topics from building a network to the different procedures you need to follow to secure it. You'll first be introduced to different packages and libraries, before moving on to different ways to build a network with the help of Python scripting. Later, you will learn how to check a network's vulnerability using Python security scripting, and understand how to check vulnerabilities in your network. As you progress through the chapters, you will also learn how to achieve endpoint protection by leveraging Python packages along with writing forensic scripts. By the end of this book, you will be able to get the most out of the Python language to build secure and robust networks that are resilient to attacks. What you will learn Develop Python scripts for automating security and pentesting tasks Discover the Python standard library's main modules used for performing security-related tasks Automate analytical tasks and the extraction of information from servers Explore processes for detecting and exploiting vulnerabilities in servers Use network software for Python programming Perform server scripting and port scanning with Python Identify vulnerabilities in web applications with Python Use Python to extract metadata and forensics Who this book is for This book is ideal for network engineers, system administrators, or any security professional looking at tackling networking and security challenges. Programmers with some prior experience in Python will get the most out of this book. Some basic understanding of general programming structures and Python is required. Downloading the example code for this book You can dow ...